(untitled) (Journal of Parents and Teachers, 2017)
The need to integrate innovation lines has to lead us to forge experiences in which, as in this case, we work with a strategy, that of Projects, which is applied with the development of methodology of thought, Multiple Intelligences and Key Competences. A whole Stage and a Team of teachers with an organizational and methodological strategy that can be applied flexibly, creatively and adapted to the needs and interests of different centers and situations.